2013
DOI: 10.1371/journal.pone.0073283
|View full text |Cite
|
Sign up to set email alerts
|

On the Edge: Haptic Discrimination of Edge Sharpness

Abstract: The increasing ubiquity of haptic displays (e.g., smart phones and tablets) necessitates a better understanding of the perceptual capabilities of the human haptic system. Haptic displays will soon be capable of locally deforming to create simple 3D shapes. This study investigated the sensitivity of our haptic system to a fundamental component of shapes: edges. A novel set of eight high quality shape stimuli with test edges that varied in sharpness were fabricated in a 3D printer. In a two alternative, forced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…We formalized this observation by applying a model selection technique to our psychophysical data (Skinner et al, 2013; Kent et al, 2014). In addition to our probit function, with its two parameters (location and spread), we employed an additional random button press model.…”
Section: Discussionmentioning
confidence: 99%
“…We formalized this observation by applying a model selection technique to our psychophysical data (Skinner et al, 2013; Kent et al, 2014). In addition to our probit function, with its two parameters (location and spread), we employed an additional random button press model.…”
Section: Discussionmentioning
confidence: 99%
“…These cells respond to sustained skin deformation from points, edges, and curvature, and respond linearly to the depth of indentation (eg Phillips & Johnson, 1981); SA2 receptors are much more sensitive to stretch than indentation, so likely play a lesser role. However, our previous study (Skinner et al, 2013) demonstrated that discrimination relying on a static touch-a strategy for exploration that, because of its relatively slow and sustained nature, is likely to activate predominately SA1 receptors-resulted in poorer discrimination of edge sharpness than more active strategies, which are likely to additionally recruit more rapidly adapting receptors. It therefore seems likely that perception of edge sharpness additionally benefits from input from rapidly adapting mechanoreceptors that respond to dynamic touch (and are insensitive to static touch).…”
Section: Introductionmentioning
confidence: 89%
“…In particular, the sharpness of an edge, defined as the angle at which two faces meet, as distinct from the curvature of an object (see Kappers, 2011, for a review of curvature), has been underexplored. In one study directly investigating edge sharpness, Skinner et al (2013) showed that perception of edge sharpness was affected by exploration strategy. Specifically, Skinner et al found that the discrimination threshold for the sharpness of an edge (using only the index finger) decreased when participants were allowed to explore the edge using a relatively free exploration strategy with the index finger compared with when participants were allowed only a single static touch of the edge.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations